Peking prognostic score is a useful prognostic factor in patients with gastric cancer liver metastases receiving hepatectomy - Xiong, Jianping; Wu, Yunzi; Hu, Haitao; Kang, Wenzhe; Li, Yang; Jin, Peng; Shao, Xinxin; Li, Weikun; Xie, Yibin; Tian, Yantao (Frontiers in Nutrition, 2022)
Background: The present work evaluated how Peking prognostic score (PPS), the new prognostic index determined according to sarcopenia as well as lymphocyte-to-C-reactive protein ratio (LCR) was prognostic factor for gastric cancer liver metastases (GCLM) patients who received hepatectomy. Methods: This work extracted information in GCLM patients undergoing hepatectomy from June 2012 to May 2018. The PPS of the patients was calculated from sarcopenia status and LCR before surgery, and patients were then divided as three groups based on their PPS. This work also carried out univariate as well as multivariate analysis for identifying variables linked with overall survival (OS) together with recurrence-free survival (RFS) after hepatectomy among three groups according to PPS. Results: This work included 108 GCLM cases who received hepatectomy. All cases were classified as 3 groups., including 26 (24.1%), 48 (44.4%) and 34 (31.5%) in groups 0-2, separately. PPS exhibited positive relation to age (P< 0.001), body mass index (P=0.012) and liver metastasis number. The relapse rates after hepatectomy in patients with GCLM was 69.4%. Additionally, the remnant liver relapse rates of groups 0-2 were 80.0%, 68.7% and 53.5%. Patients in group 0 had significantly increased remnant liver relapse rate compared with those in groups 0 and 1. PPS was significantly related to relapse pattern (P= 0.003). Relative to group 0, those of the other 2 groups showed dismal OS (HR=3.98, 7.49 for groups 1 and 2; p<0.001) along with RFS (HR=3.65, 5.33 for groups 1 and 2; p<0.001). As revealed by multivariate analysis, PPS independently predicted OS (P< 0.001) together with RFS (P< 0.001). Conclusions: The PPS could be an easy nutrition-inflammation prognostic scoring system and an independent preoperative predictor of survival for GCLM cases after hepatectomy.